Are poor, remote areas left behind in agricultural development: the case of Tanzania - Minot, Nicholas (International Food Policy Research Institute, 2005)
In Tanzania, as in many other developing countries, the conventional wisdom is that economic reforms may have stimulated economic growth, but that the benefits of this growth have been uneven, favoring urban households and farmers with good market access. This idea, although quite plausible, has rarely been tested empirically. In this paper, we develop a new approach to measuring trends in poverty and apply it to Tanzania in order to explore the distributional aspects of economic growth and the relationship between rural poverty and market access. We find that, between 1991 and 2003, a period of extensive economic reforms, the overall rate of poverty fell about 9 percentage points. The degree of poverty reduction was similar between rural and urban areas, though poverty appears not to have declined in Dar es Salaam. The poverty rate fell more among households with a less educated head of household than among those with a more educated head. The gains were greater among male-headed households than female-headed households. We find that rural poverty is associated with remoteness, but the relationship is surprisingly weak and it varies depending on the definition used. Rural poverty is more closely related to access to regional urban centers than distance to roads or to Dar es Salaam. We find little evidence that remote rural areas are being “left behind” in terms of the absolute decline in the poverty rate.